Equation of state and some other properties of rock-salt AlN - Daoud, Salah; Mezouar, Rabie; Benmakhlouf, Abdelfateh (International Journal of Physical Research, 2018)
The object of the present work is to study the equation of state (EOS) and the temperature dependence of the vibrational constant pressure heat capacity, the adiabatic bulk modulus Bs and the pressure derivative of the isothermal bulk modulus of cubic rock-salt Aluminum nitride under high pressure up to 100 GPa. In addition, the isothermal bulk modulus and the Debye temperature Î¸D versus pressure at 1800 K are presented. Some structural and thermophysical properties used here are taken from our previous paper published in J. Electron. Mater. (2018) DOI: 10.1007/s11664-018-6169-x. The results obtained are analyzed and compared with other data of the literature.Â Â